OpenSHMEM and related technologies : experiences, implementations, and technologies : second workshop, OpenSHMEM 2015, Annapolis, MD, USA, August 4-6, 2015. Revised selected papers /: experiences, implementations, and technologies : second workshop, OpenSHMEM 2015, Annapolis, MD, USA, August 4-6, 2015. Revised selected papers. (2015) - Unknown
No abstract available